Depressive symptoms in adolescents from the brazilian midwest: Prevalence and association with sociodemographic characteristics (Revista Contexto & Saúde, 2026)
Objective: To estimate the prevalence of depressive symptoms and investigate their association with sociodemographic characteristics among adolescents in the Brazilian Midwest. Method: Study using data from the National School Health Survey (2019). The dependent variables were depressive symptoms and negative self-assessment mental health. Prevalence and prevalence ratios were estimated according to sex, age group, administrative dependence on the school, and goods and services score. Results: 17,640 students aged 13 to 17 years from the region Midwest were evaluated. 54.0% of adolescents reported feelings of worry, 34.0% felt sad, 31.1% felt that nobody cared about them, 43.3% reported feelings of irritation/nervousness/bad mood, 22.8% felt that life was not worth living, and 19.6% of adolescents presented a negative self-assessment mental health. The highest prevalences of depressive symptoms, as represented by the evaluated indicators, were observed in females aged 16 or 17, students from public schools, and those with a low score on goods and services. Conclusion: Depressive symptoms among adolescents in the region Midwest were associated with sociodemographic characteristics, representing challenges to mental health care for this population group.
Keywords: Mental Health; Depression; Adolescent; Socioeconomic Factors